When should surgeons retire?. Issue 1 (18th November 2015) - Bhatt, N R; Morris, M; O'Neil, A; Gillis, A; Ridgway, P F
Abstract: Background: Retirement policies for surgeons differ worldwide. A range of normal human functional abilities decline as part of the ageing process. As life expectancy and their population increases, the performance ability of ageing surgeons is now a growing concern in relation to patient care. The aim was to explore the effects of ageing on surgeons' performance, and to identify current practical methods for transitioning surgeons out of practice at the appropriate time and age. Methods: A narrative review was performed in MEDLINE using the terms 'ageing' and 'surgeon'. Additional articles were hand-picked. Modified PRISMA guidelines informed the selection of articles for inclusion. Articles were included only if they explored age-related changes in brain biology and the effect of ageing on surgeons' performance. Results: The literature search yielded 1811 articles; of these, 36 articles were included in the final review. Wide variation in ability was observed across ageing individuals (both surgical and lay). Considerable variation in the effects of the surgeon's age on patient mortality and postoperative complications was noted. A lack of neuroimaging research exploring the ageing of surgeons' brains specifically, and lack of real markers available for measuring surgical performance, both hinder further investigation. Standard retirement policies in accordance with age-related surgical ability are lacking in most countries around the world. Conclusion: Competence should be assessed at an individual level, focusing on functional ability over chronological age; this should inform retirement policies for surgeons. Abstract : Should be decided individually